High impact nylon composite and method of making same

CN122706138BActive Publication Date: 2026-10-09NANJING LIHUA ENG PLASTIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611207255.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-09
Estimated Expiration
2046-08-11

AI Technical Summary

Technical Problem

[0006]针对现有高抗冲击的尼龙复合材料中增韧相与尼龙基体界面作用过强时易限制弹性体相空穴化,而单纯增加增韧组分用量又容易降低材料基本力学性能和加工稳定性的问题,本申请提供一种高抗冲击的尼龙复合材料及其制备方法

Benefits of technology

本申请通过界面调节剂、硬脂酸锌、硬脂酸和改性纳米二氧化硅共同构建弹性体相界面结构,使马来酸酐接枝聚烯烃弹性体与尼龙基体之间形成兼具有限锚定和局部滑移能力的界面层,能够缓解界面作用过强导致弹性体相被过度束缚的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122706138B_ABST
    Figure CN122706138B_ABST
Patent Text Reader

Abstract

The application provides a high-impact nylon composite material and a preparation method thereof, and belongs to the technical field of polymer composite materials. The composite material takes PA66 / PA6 as a main matrix material, toughening mother particles are prepared from modified nano-silicon dioxide, an interface adjusting agent, zinc stearate, stearic acid, deionized water and a maleic anhydride grafted polyolefin elastomer, and then the toughening mother particles are melt-blended with a pre-dried nylon matrix to obtain the composite material. The interface adjusting agent can be used in combination with the modified nano-silicon dioxide, the zinc stearate and the maleic anhydride grafted polyolefin elastomer, which is beneficial to forming an interface structure with certain stress transmission and local slip ability between the elastomer phase and the nylon matrix. The interface structure is beneficial to reducing the degree of excessive constraint of the elastomer phase, and improving the interface stress release and crack blunting process under the impact condition, so as to improve the notched impact performance and low-temperature impact performance of the nylon composite material, and meanwhile, the mechanical performance and processing stability of the material are considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer composite materials technology, and relates to a high-impact nylon composite material and its preparation method. Background Technology

[0002] Nylon materials possess good mechanical strength, wear resistance, oil resistance, and processing properties, and are widely used in automotive parts, electronic and electrical structural components, mechanical connectors, and industrial housings. However, under dry, low-temperature, or notched conditions, the chain segment movement capability of nylon materials is limited, and cracks tend to propagate rapidly under impact loads, resulting in insufficient notched impact resistance and limiting its further application in high-impact structural components.

[0003] In existing technologies, the impact toughness of nylon materials is typically improved by adding elastomers, rubber phases, core-shell toughening agents, or other toughening components to the nylon matrix. These methods primarily focus on enhancing the compatibility and dispersion uniformity between the toughening phase and the nylon matrix to improve interfacial bonding and reduce phase separation defects. However, in actual impact testing, the toughening phase not only needs to form a strong bond with the nylon matrix, but also requires moderate deformation, interfacial energy dissipation, and cavitation under crack tip stress, thereby inducing shear yielding in the nylon matrix and blunting the crack.

[0004] If the interfacial interaction between the toughening phase and the nylon matrix is ​​too strong, the toughening phase may be excessively bound by the rigid matrix, making it difficult to form effective microcavities and stress release zones under notched or low-temperature impact conditions, thus limiting the toughening efficiency. On the other hand, simply increasing the amount of toughening component to improve impact performance can easily reduce the material's rigidity, heat resistance, and dimensional stability, making it difficult for the material to meet the comprehensive performance requirements of structural components.

[0005] Therefore, how to construct an interface energy-dissipating structure that can achieve local stress release, moderate cavitation and crack passivation under impact load while maintaining the basic strength, flexural load-bearing capacity and processing adaptability of nylon composites remains a problem that needs to be solved for high impact-resistant nylon composites. Summary of the Invention

[0006] To address the problem that excessively strong interfacial interactions between the toughening phase and the nylon matrix in existing high-impact nylon composites can restrict cavitation in the elastomer phase, while simply increasing the amount of toughening components can easily reduce the basic mechanical properties and processing stability of the material, this application provides a high-impact nylon composite material and its preparation method. This method involves first preparing a toughening masterbatch, then melt-blending it with a PA66 / PA6 nylon matrix. This allows the interface modifier, zinc stearate, and modified nano-silica to participate more effectively in the construction of the interfacial structure near the elastomer phase, thereby forming an interfacial structure with certain stress transfer and local slip capabilities.

[0007] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high-impact nylon composite material, wherein the high-impact nylon composite material is obtained by melt blending a pre-dried nylon matrix, a toughening masterbatch, and a compounded antioxidant; the pre-dried nylon matrix is ​​composed of PA66 and PA6; the toughening masterbatch is obtained by reactive extrusion of maleic anhydride-grafted polyolefin elastomer, an interface modifier, zinc stearate, modified nano-silica, stearic acid, deionized water, and a compounded antioxidant.

[0008] The modified nano-silica is obtained by modifying nano-silica with 3-aminopropyltriethoxysilane; the interface modifier is obtained by reacting monoglycidyl ether-terminated polydimethylsiloxane and biamino-terminated polyetheramine; the maleic anhydride-grafted polyolefin elastomer is any one of maleic anhydride-grafted POE, maleic anhydride-grafted EOR, or maleic anhydride-grafted EPDM.

[0009] Secondly, this application also provides a method for preparing a high-impact nylon composite material, comprising the following steps: S1: After drying, nano-silica is dispersed in a mixed solvent, the pH is adjusted and ultrasonically dispersed, 3-aminopropyltriethoxysilane is added to react, and after centrifugation, washing and drying, modified nano-silica is obtained. S2: A monoglycidyl ether-terminated polydimethylsiloxane and a diamino-terminated polyetheramine are reacted under nitrogen protection and then vacuum devoured to obtain an interface modifier; S3: Mix the interface modifier, zinc stearate, modified nano silica, stearic acid and deionized water to obtain a premix; dry the maleic anhydride-grafted polyolefin elastomer and knead it with the premix to obtain an elastomer premix; react and extrude the elastomer premix and compound antioxidant to obtain toughening masterbatch. S4: PA66 and PA6 are mixed and dried to obtain a pre-dried nylon matrix; the pre-dried nylon matrix, toughening masterbatch and compound antioxidant are mixed and melt-blended to obtain a high-impact nylon composite material.

[0010] Preferably, in step S1, nano-silica is vacuum dried at 100-120℃ for 2-4 hours to obtain pre-dried nano-silica; the volume ratio of ethanol to water in the mixed solvent is (80-95):(5-20), and the mass-volume ratio of pre-dried nano-silica to the mixed solvent is 1g:(20-60)mL; acetic acid is added to adjust the pH to 4.0-5.5; ultrasonic dispersion is performed for 20-60 minutes; the mass ratio of 3-aminopropyltriethoxysilane to pre-dried nano-silica is (3-10):100; the reaction temperature is 45-70℃, the reaction time is 3-6 hours, the drying temperature is 70-90℃, and the drying time is 6-12 hours.

[0011] Preferably, in step S2, the number average molecular weight of the monoglycidyl ether-terminated polydimethylsiloxane is 800-3000; the diamino-terminated polyetheramine is polyetheramine D-230 or polyetheramine D-400; the ratio of the molar number of epoxy groups derived from the monoglycidyl ether-terminated polydimethylsiloxane to the molar number of diamino-terminated polyetheramine molecules is 1:(1.2-2); the reaction temperature is 60-90℃, and the reaction time is 3-8h; the vacuum devolatilization temperature is 80-100℃, the vacuum degree is -0.08~-0.095MPa, and the vacuum devolatilization time is 0.5-2h.

[0012] Preferably, in step S3, the maleic anhydride grafting rate of the maleic anhydride-grafted polyolefin elastomer is 0.3-0.8 wt%; the mixing temperature of the interface modifier, zinc stearate, modified nano-silica, stearic acid, and deionized water is 40-70℃, and the mixing time is 10-30 min; the drying temperature of the maleic anhydride-grafted polyolefin elastomer is 60-90℃, and the drying time is 2-4 h; the kneading temperature of the premix is ​​50-80℃, and the kneading time of the premix is ​​20-60 min; the parameters of the reactive extrusion are: temperature 175-210℃, screw speed 150-320 rpm, material residence time 1-4 min, and vacuum exhaust pressure -0.06~-0.095 MPa. The vacuum exhaust is located in the middle or later stage of the reactive extrusion, allowing trace amounts of deionized water to participate in the ring-opening of some anhydride groups in the molten reaction section before being discharged through vacuum exhaust.

[0013] Preferably, in step S3, the mass ratio of the pre-dried elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant is 100:(10-14):(1.5-3):(3-6):(0.05-0.3):(0.05-0.2):(0.5-1.2); the compound antioxidant is obtained by compounding antioxidant 1098 and antioxidant 168 in a mass ratio of (1-3):1.

[0014] Preferably, in step S4, the mass ratio of PA66 to PA6 is (70-90):(10-30); after mixing PA66 and PA6, the mixture is vacuum dried at 90-110℃ for 8-12 hours to obtain a pre-dried nylon matrix; the mass ratio of the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant is 100:(14-20):(0.15-0.35).

[0015] Preferably, in step S4, the parameters for melt blending are: extrusion temperature of 250-285℃; wherein, when the mass percentage of PA6 in the nylon matrix is ​​greater than 20%, the extrusion temperature is 250-275℃; when the mass percentage of PA6 in the nylon matrix is ​​10-20%, the extrusion temperature is 260-285℃; screw speed is 180-350 rpm; material residence time is 1-3 min; and vacuum exhaust pressure is -0.06~-0.095 MPa.

[0016] This application does not simply improve the compatibility between maleic anhydride-grafted polyolefin elastomers and nylon matrices, nor does it simply increase the amount of elastomer to improve impact toughness. Instead, it utilizes a pre-construction method with toughening masterbatch to form an interfacial energy-dissipating structure between the elastomer phase and the nylon matrix, possessing certain stress transfer and local stress release capabilities. This structure also helps to improve the cavitation energy dissipation process under impact loads. This interfacial structure helps maintain the interfacial interaction between the elastomer phase and the nylon matrix under normal stress conditions and provides conditions for elastomer phase deformation, interfacial stress release, and energy-dissipating deformation of the nylon matrix under impact loads, thereby alleviating the problem of excessive binding of the elastomer phase in strong interfacial toughening systems.

[0017] First, in step S1, after the nano-silica is modified with 3-aminopropyltriethoxysilane, an aminosilane layer is introduced onto its surface. This modification helps reduce the agglomeration tendency of nano-silica in the organic phase and improves its interaction with subsequent interface modifiers and maleic anhydride-grafted polyolefin elastomers. Furthermore, the amino and siloxane structures on the surface of the modified nano-silica can participate in polar interactions or hydrogen bonding near the elastomer phase interface, making it more conducive to the structural construction of the elastomer phase and its interface region along with the toughening masterbatch compared to direct blending. Therefore, the modified nano-silica can act as an interface support and micro-area stress dispersion regulator in the system, and is beneficial for interface energy dissipation and crack passivation during impact.

[0018] Secondly, in step S2, monoglycidyl ether-terminated polydimethylsiloxane reacts with diamino-terminated polyetheramine to form an interface modifier. This interface modifier contains polydimethylsiloxane segments, polyether segments, hydroxyl groups formed by epoxy ring-opening, and retained amino reactive sites. The polydimethylsiloxane segments possess good flexibility and low cohesive energy, providing local slip and stress buffer space for the interface; the polyether segments enhance the compatibility of the interface modifier with the nylon phase and polar interface components; the hydroxyl and amino reactive sites can produce limited reactions or polar interactions with the anhydride groups in the maleic anhydride-grafted polyolefin elastomer, the carboxyl groups after anhydride ring-opening, and the nylon end groups. Therefore, this interface modifier facilitates the formation of a transition interface with flexible segments between the elastomer phase and the nylon matrix, thus distinguishing it from a single strongly reactive interface.

[0019] Next, in step S3, the interface modifier, zinc stearate, modified nano-silica, stearic acid, and deionized water are premixed and then kneaded and reacted with the pre-dried elastomer to prepare toughening masterbatch. This step facilitates greater participation of the interface modifier, zinc stearate, and modified nano-silica in the interfacial structure construction around the maleic anhydride-grafted polyolefin elastomer. The addition of stearic acid and trace amounts of deionized water does not ensure complete reaction of the anhydride groups during the premixing stage, but rather allows the deionized water to be distributed as trace amounts of adsorbed water in the premixed system formed by zinc stearate, modified nano-silica, and the interface modifier. In the subsequent melt reaction section of the reacted extrusion, the trace amounts of adsorbed water contact some of the anhydride groups in the maleic anhydride-grafted polyolefin elastomer, which is beneficial for forming a small amount of open-ring carboxyl structures. Subsequently, zinc stearate can coordinate with the open-ring carboxyl groups, stearate groups, or interfacial polar groups, thereby facilitating the formation of rearrangeable stress transfer micro-regions at the interface. Residual water is then removed through vacuum degassing. This coordination effect differs from rigid chemical crosslinking; it facilitates physical bonding and stress transfer at the interface and exhibits localized stress release characteristics under impact loads. Consequently, the elastomer interface is no longer a simple strongly bonded interface or a weakly debonded interface, but rather forms a moderately strong interface that combines bonding, buffering, and rearrangement characteristics.

[0020] Meanwhile, modified nano-silica, together with interface modifiers and zinc stearate, participates in the construction of the interfacial structure near the elastomer phase in the toughening masterbatch, which is beneficial for forming a point-like support structure around the elastomer phase. Under impact load, the elastomer phase and the vicinity of the interface are subjected to local triaxial tensile stress transmitted from the crack tip. If the interfacial bonding is too strong, the elastomer phase is not easy to form effective cavitation; if the interfacial bonding is too weak, it is easy to directly debond and form defects. This application, through the local slippage of polyether siloxane segments, stress regulation by the related coordination of zinc stearate, and point-like support of modified nano-silica, is conducive to the moderate deformation and stress release of the elastomer phase near the interface, reducing the risk of disordered debonding or excessive binding. The above-mentioned interfacial structure is conducive to releasing local stress concentration near the crack tip and promoting crack passivation and energy-dissipating deformation of the surrounding nylon matrix.

[0021] In step S4, the toughening masterbatch is melt-blended with the pre-dried nylon matrix formed by PA66 / PA6. Because the toughening masterbatch in the early stage makes the interface modifier, zinc stearate, and modified nano-silica more conducive to participating in the construction of the composite interface structure near the elastomer phase, these functional components are more likely to enter the nylon matrix along with the elastomer phase and participate in the structural construction of the elastomer phase interface region during subsequent melt blending with the nylon matrix. This reduces the insufficient interface regulation caused by completely random dispersion. PA66 provides good strength and heat resistance, while PA6 improves the processing fluidity and certain toughness of the system; together, they form a continuous nylon matrix. The maleic anhydride-grafted polyolefin elastomer in the toughening masterbatch is distributed as a dispersed phase within this continuous matrix. The interface modifier and zinc ion coordination microregions form a transition layer between the elastomer phase and the nylon matrix, giving the interface moderate bonding strength. The modified nano-silica is beneficial for providing point-like support and stress dispersion regulation near the interface.

[0022] In this application, the components are not simply added in parallel, but rather form a synergistic relationship: maleic anhydride-grafted polyolefin elastomer provides an elastomer phase capable of deformation and cavitation; the interface modifier constructs a locally slipping buffer interface through polydimethylsiloxane and polyether segments, and achieves limited anchoring through reactive or polar sites such as amino and hydroxyl groups; zinc stearate forms zinc ion coordination microregions with the participation of stearic acid and trace amounts of deionized water, providing stress transfer points for interface rearrangement; modified nano-silica serves as a point-like support structure near the interface, which facilitates more dispersed microregion deformation and cavitation processes and reduces the risk of local instability propagation. After pre-positioning by the toughening masterbatch, the above components together form an interface energy-dissipating structure with the characteristics of "limited anchoring-local slip-coordination-stress dispersion".

[0023] When subjected to notched or cryogenic impact, the stress at the crack tip initially acts on the elastomer phase and its interface region. The flexible segments in the interface modifier can buffer some stress concentration, the coordination effect of zinc stearate is beneficial for interface stress regulation, and the modified nano-silica can provide support sites for micro-deformation near the elastomer phase, which helps reduce local stress concentration near the crack tip and promotes crack passivation and energy-dissipating deformation in the nylon matrix, thereby improving the impact response. Compared with nylon toughening systems that simply pursue strong interfacial compatibility, the interface structure of this application emphasizes the formation of controllable stress release and cavitation triggering conditions during impact. Compared with the approach of simply increasing the amount of elastomer, this application improves the toughening effect through interface structure regulation, which is beneficial for maintaining the flexural load-bearing capacity and processing stability of nylon composite materials while improving impact toughness.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: This application constructs an elastomer phase interface structure by using an interface modifier, zinc stearate, stearic acid, and modified nano-silica. This results in an interface layer between the maleic anhydride-grafted polyolefin elastomer and the nylon matrix that has both limited anchoring and local slippage capabilities, which can alleviate the problem of excessive binding of the elastomer phase due to excessively strong interfacial interactions.

[0025] In this application, the coordination effect of zinc stearate is beneficial to the formation of stress transfer micro-regions at the interface between the elastomer phase and the nylon matrix, so that the interface maintains a certain bonding under normal stress conditions and exhibits a certain local stress release capability under impact load, thus distinguishing it from a single strong reactive interface toughening system.

[0026] The modified nano-silica in this application participates in the construction of the elastomer phase interface along with the toughening masterbatch. It can serve as a confined structure near the interface. Combined with polyether siloxane slip segments and zinc ion coordination micro-regions, it is beneficial for micro-region stress dispersion and crack passivation during impact, and reduces the risk of local debonding or unstable propagation.

[0027] This application utilizes an interface energy-dissipating structure characterized by "limited anchoring, local slippage, coordination adjustment, and stress dispersion" to facilitate moderate deformation of the elastomer phase under notched or low-temperature impact conditions, release of interface stress, and crack passivation, while promoting energy-dissipating deformation of the nylon matrix. This improves the impact response of nylon composites without solely relying on increasing the amount of toughening components. Attached Figure Description

[0028] Figure 1 This is a physical image of the high-impact nylon composite material prepared in Example 1 of the present invention. Detailed Implementation

[0029] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include any obvious substitutions and modifications made to the embodiments described herein.

[0030] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing.

[0031] The nano-silica used in the embodiments and comparative examples of this invention is fumed nano-silica or precipitated nano-silica, and the average primary particle size of the nano-silica is 7-50 nm.

[0032] Example 1 This embodiment provides a high-impact nylon composite material and its preparation method, the preparation method specifically including the following steps: S1: Pre-dried nano-silica was obtained by vacuum drying at 110℃ for 3h; the pre-dried nano-silica was dispersed in a mixed solvent, wherein the volume ratio of ethanol to water in the mixed solvent was 90:8, and the mass-volume ratio of pre-dried nano-silica to the mixed solvent was 1g:40mL; acetic acid was added to adjust the pH to 5.0, and the mixture was ultrasonically dispersed for 45min to obtain a nano-silica dispersion; 3-aminopropyltriethoxysilane was added to the nano-silica dispersion, wherein the mass ratio of 3-aminopropyltriethoxysilane to pre-dried nano-silica was 5:100; the mixture was stirred at 60℃ for 4h; after centrifugation and washing, it was vacuum dried at 80℃ for 9h to obtain modified nano-silica; S2: Glycidyl ether-terminated polydimethylsiloxane and diamino-terminated polyetheramine (polyetheramine D-230) were added to a reaction vessel, wherein the molar ratio of epoxy groups from the glycidyl ether-terminated polydimethylsiloxane to the molar ratio of diamino-terminated polyetheramine molecules was 1:1.5. The reaction was carried out under nitrogen protection at 75°C for 5 hours with stirring. After the reaction was completed, the mixture was vacuum devolatilized at 90°C and -0.085 MPa for 1 hour to obtain the interface modifier. S3: An interface modifier, zinc stearate, modified nano-silica, stearic acid, and deionized water were stirred at 55°C for 20 minutes to obtain a premix. Maleic anhydride-grafted polyolefin elastomer (POE) was vacuum-dried at 70°C for 3 hours to obtain a pre-dried elastomer. The premix and pre-dried elastomer were then added to a low-speed kneader and kneaded at 65°C for 40 minutes to obtain an elastomer premix. The elastomer premix and compounded antioxidant were added to a twin-screw extruder for reactive extrusion at an extrusion temperature of [temperature missing]. The temperature was 190℃, the screw speed was 250 rpm, the material residence time was 2 min, and the vacuum exhaust pressure was -0.07 MPa. After extrusion, water cooling, and pelletizing, toughening masterbatch was obtained. The mass ratio of pre-dried elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant was 100:12:2:4:0.15:0.1:0.8. The compound antioxidant was obtained by compounding antioxidant 1098 and antioxidant 168 in a mass ratio of 2:1. S4: PA66 and PA6 are mixed at a mass ratio of 80:20 and vacuum dried at 100℃ for 10 hours to obtain a pre-dried nylon matrix; the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant (obtained by compounding antioxidant 1098 and antioxidant 168 at a mass ratio of 2:1) are mixed to obtain a premix, wherein the mass ratio of the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant is 100:17:0.25; the premix is ​​added to a twin-screw extruder for melt blending, the extrusion temperature is 270℃, the screw speed is 250 rpm, the material residence time is 2 min, and the vacuum exhaust pressure is -0.08 MPa. After extrusion, water cooling, and pelletizing, the following is obtained: Figure 1 The high-impact nylon composite material shown.

[0033] Example 2 This embodiment provides a high-impact nylon composite material and its preparation method, the preparation method specifically including the following steps: S1: Pre-dried nano-silica was obtained by vacuum drying at 100℃ for 2h; the pre-dried nano-silica was dispersed in a mixed solvent, wherein the volume ratio of ethanol to water in the mixed solvent was 80:10, and the mass-volume ratio of pre-dried nano-silica to the mixed solvent was 1g:20mL; acetic acid was added to adjust the pH to 4.0, and the mixture was ultrasonically dispersed for 20min to obtain a nano-silica dispersion; 3-aminopropyltriethoxysilane was added to the nano-silica dispersion, wherein the mass ratio of 3-aminopropyltriethoxysilane to pre-dried nano-silica was 3:100; the mixture was stirred at 45℃ for 3h; after centrifugation and washing, it was vacuum dried at 70℃ for 6h to obtain modified nano-silica; S2: Glycidyl ether-terminated polydimethylsiloxane and diamino-terminated polyetheramine (polyetheramine D-400) were added to a reaction vessel, wherein the molar ratio of epoxy groups from the glycidyl ether-terminated polydimethylsiloxane to the molar ratio of diamino-terminated polyetheramine molecules was 1:1.2. The reaction was carried out under nitrogen protection at 60°C with stirring for 3 hours. After the reaction was completed, the mixture was vacuum devolatilized at 80°C and -0.08 MPa for 0.5 hours to obtain the interface modifier. S3: An interface modifier, zinc stearate, modified nano-silica, stearic acid, and deionized water were stirred at 40°C for 10 minutes to obtain a premix. Maleic anhydride-grafted polyolefin elastomer (EOR-grafted with maleic anhydride) was vacuum-dried at 60°C for 2 hours to obtain a pre-dried elastomer. The premix and pre-dried elastomer were then added to a low-speed kneader and kneaded at 50°C for 20 minutes to obtain an elastomer premix. The elastomer premix and compounded antioxidant were added to a twin-screw extruder for reactive extrusion at an extrusion temperature of [temperature missing]. At 175℃, with a screw speed of 150 rpm, a material residence time of 1 min, and a vacuum exhaust pressure of -0.06 MPa, toughening masterbatch was obtained after extrusion, water cooling, and pelleting. The mass ratio of pre-dried elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant was 100:10:1.5:3:0.05:0.05:0.5. The compound antioxidant was obtained by compounding antioxidant 1098 and antioxidant 168 in a mass ratio of 1:1. S4: PA66 and PA6 are mixed at a mass ratio of 70:10 and vacuum dried at 90℃ for 8 hours to obtain a pre-dried nylon matrix; the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant (obtained by compounding antioxidant 1098 and antioxidant 168 at a mass ratio of 1:1) are mixed to obtain a premix, wherein the mass ratio of the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant is 100:14:0.15; the premix is ​​added to a twin-screw extruder for melt blending, the extrusion temperature is 260℃, the screw speed is 180rpm, the material residence time is 1min, and the vacuum exhaust pressure is -0.06MPa. After extrusion, water cooling, and pelletizing, a high-impact nylon composite material is obtained.

[0034] Example 3 This embodiment provides a high-impact nylon composite material and its preparation method, the preparation method specifically including the following steps: S1: Pre-dried nano-silica was obtained by vacuum drying at 120℃ for 4 h; the pre-dried nano-silica was dispersed in a mixed solvent, wherein the volume ratio of ethanol to water in the mixed solvent was 95:5, and the mass-volume ratio of pre-dried nano-silica to the mixed solvent was 1 g:60 mL; acetic acid was added to adjust the pH to 5.5, and the mixture was ultrasonically dispersed for 60 min to obtain a nano-silica dispersion; 3-aminopropyltriethoxysilane was added to the nano-silica dispersion, wherein the mass ratio of 3-aminopropyltriethoxysilane to pre-dried nano-silica was 10:100; the mixture was stirred at 70℃ for 6 h; after centrifugation and washing, it was vacuum dried at 90℃ for 12 h to obtain modified nano-silica; S2: Glycidyl ether-terminated polydimethylsiloxane and diamino-terminated polyetheramine (polyetheramine D-400) were added to a reaction vessel, wherein the molar ratio of epoxy groups from the glycidyl ether-terminated polydimethylsiloxane to the molar ratio of diamino-terminated polyetheramine molecules was 1:2. The reaction was carried out under nitrogen protection at 90°C with stirring for 8 hours. After the reaction was completed, the mixture was vacuum devolatilized at 100°C and -0.095MPa for 2 hours to obtain the interface modifier. S3: An interface modifier, zinc stearate, modified nano-silica, stearic acid, and deionized water were stirred at 70°C for 30 minutes to obtain a premix. Maleic anhydride-grafted polyolefin elastomer and maleic anhydride-grafted EPDM were vacuum dried at 90°C for 4 hours to obtain a pre-dried elastomer. The premix and pre-dried elastomer were then added to a low-speed kneader and kneaded at 80°C for 60 minutes to obtain an elastomer premix. The elastomer premix and compounded antioxidant were added to a twin-screw extruder for reactive extrusion at an extrusion temperature of [temperature missing]. The temperature was 210℃, the screw speed was 320rpm, the material residence time was 4min, and the vacuum exhaust pressure was -0.095MPa. After extrusion, water cooling, and pelletizing, toughening masterbatch was obtained. The mass ratio of pre-dried elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant was 100:14:3:6:0.3:0.2:1.2. The compound antioxidant was obtained by compounding antioxidant 1098 and antioxidant 168 in a mass ratio of 3:1. S4: PA66 and PA6 are mixed at a mass ratio of 90:30 and vacuum dried at 110℃ for 12h to obtain a pre-dried nylon matrix; the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant (obtained by compounding antioxidant 1098 and antioxidant 168 at a mass ratio of 3:1) are mixed to obtain a premix, wherein the mass ratio of the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant is 100:20:0.35; the premix is ​​added to a twin-screw extruder for melt blending, the extrusion temperature is 275℃, the screw speed is 350rpm, the material residence time is 3min, and the vacuum exhaust pressure is -0.095MPa. After extrusion, water cooling, and pelletizing, a high-impact nylon composite material is obtained.

[0035] Example 4 This embodiment provides a high-impact nylon composite material and its preparation method, the preparation method specifically including the following steps: S1: Pre-dried nano-silica was obtained by vacuum drying at 115℃ for 3.5h; the pre-dried nano-silica was dispersed in a mixed solvent, wherein the volume ratio of ethanol to water in the mixed solvent was 85:7, and the mass-volume ratio of pre-dried nano-silica to the mixed solvent was 1g:50mL; acetic acid was added to adjust the pH to 4.5, and the mixture was ultrasonically dispersed for 30min to obtain a nano-silica dispersion; 3-aminopropyltriethoxysilane was added to the nano-silica dispersion, wherein the mass ratio of 3-aminopropyltriethoxysilane to pre-dried nano-silica was 8:100; the mixture was stirred at 55℃ for 5h; after centrifugation and washing, it was vacuum dried at 85℃ for 10h to obtain modified nano-silica; S2: Glycidyl ether-terminated polydimethylsiloxane and diamino-terminated polyetheramine (polyetheramine D-230) were added to a reaction vessel, wherein the molar ratio of epoxy groups from the glycidyl ether-terminated polydimethylsiloxane to the molar ratio of diamino-terminated polyetheramine molecules was 1:1.8. The reaction was carried out under nitrogen protection at 80°C with stirring for 7 hours. After the reaction was completed, the mixture was vacuum devolatilized at 95°C and -0.09 MPa for 1.5 hours to obtain an interface modifier. S3: An interface modifier, zinc stearate, modified nano-silica, stearic acid, and deionized water were stirred at 60°C for 25 min to obtain a premix. Maleic anhydride-grafted polyolefin elastomer (POE) was vacuum-dried at 85°C for 3.5 h to obtain a pre-dried elastomer. The premix and pre-dried elastomer were then added to a low-speed kneader and kneaded at 75°C for 50 min to obtain an elastomer premix. The elastomer premix and compounded antioxidant were added to a twin-screw extruder for reactive extrusion at an extrusion temperature of [temperature missing]. The temperature was 200℃, the screw speed was 280 rpm, the material residence time was 3 min, and the vacuum exhaust pressure was -0.08 MPa. After extrusion, water cooling, and pelletizing, toughening masterbatch was obtained. The mass ratio of pre-dried elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant was 100:13:2.5:5:0.2:0.15:1.0. The compound antioxidant was obtained by compounding antioxidant 1098 and antioxidant 168 at a mass ratio of 2.5:1. S4: PA66 and PA6 are mixed at a mass ratio of 85:25 and vacuum dried at 105℃ for 11h to obtain a pre-dried nylon matrix; the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant (obtained by compounding antioxidant 1098 and antioxidant 168 at a mass ratio of 2.5:1) are mixed to obtain a premix, wherein the mass ratio of the pre-dried nylon matrix, toughening masterbatch, and compound antioxidant is 100:19:0.3; the premix is ​​added to a twin-screw extruder for melt blending, the extrusion temperature is 270℃, the screw speed is 300rpm, the material residence time is 2.5min, and the vacuum exhaust pressure is -0.09MPa. After extrusion, water cooling, and pelletizing, a high-impact nylon composite material is obtained.

[0036] Comparative Example 1 This comparative example provides a high-impact nylon composite material and its preparation method. The difference from Example 1 is that the maleic anhydride-grafted POE in S3 is replaced with maleic anhydride-grafted POE with a grafting rate of 1.2-1.5wt%. Other operating steps and process parameters are exactly the same as in Example 1.

[0037] Comparative Example 2 This comparative example provides a high-impact nylon composite material and its preparation method. The difference from Example 1 is that step S2 is omitted, and no interface modifier is added in S3. Other operation steps and process parameters are exactly the same as in Example 1.

[0038] Comparative Example 3 This comparative example provides a high-impact nylon composite material and its preparation method. The difference from Example 1 is that zinc stearate, stearic acid and deionized water are not added in S3, while other operation steps and process parameters are exactly the same as in Example 1.

[0039] Comparative Example 4 This comparative example provides a high-impact nylon composite material and its preparation method. The difference from Example 1 is that step S1 is omitted, and modified nano-silica is not added in S3. Other operation steps and process parameters are exactly the same as in Example 1.

[0040] Comparative Example 5 This comparative example provides a high-impact nylon composite material and its preparation method. The difference from Example 1 is that step S3 is omitted, and maleic anhydride-grafted POE, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant are directly added to the twin-screw extruder in S4 for melt blending. Other operation steps and process parameters are exactly the same as in Example 1.

[0041] The performance of the high-impact nylon composite materials of Examples 1-4 and Comparative Examples 1-5 was tested, and the specific process is as follows: Notched impact performance test: Injection-molded specimens obtained from each example and comparative example were used to prepare notched impact test specimens of the same size and notch radius. Notched impact strength tests were conducted at 23℃ and -30℃. The 23℃ notched impact test was performed directly after the specimens were conditioned to moisture equilibrium. Before the -30℃ notched impact test, the specimens were placed in a -30℃ environment for 4 hours, and the test was completed within 60 seconds after removal. The notched impact strength of each specimen was recorded.

[0042] Tensile property test: Take the injection-molded strips obtained from each example and comparative example, and after equilibration at 23℃ and 50%RH for 24 hours, perform tensile property test. The tensile speed is 50mm / min, and record the tensile strength.

[0043] Bending performance test: Take the injection molded specimens obtained from each example and comparative example, and after equilibration at 23℃ and 50%RH for 24h, perform a three-point bending test with a loading speed of 2mm / min, and record the bending strength.

[0044] Heat distortion temperature test: The heat distortion temperature of the samples obtained from each embodiment and comparative example was tested. The test load was 1.80 MPa, and the temperature at which the sample reached the specified deformation was recorded.

[0045] The test results are shown in Table 1.

[0046] Table 1. Performance test results of high impact-resistant nylon composite materials in Examples 1-4 and Comparative Examples 1-5

[0047] As shown in Table 1, the test results of Example 1 and Comparative Example 1 indicate that after replacing maleic anhydride-grafted POE with maleic anhydride-grafted POE with a high grafting rate, the degree of interfacial reaction between the elastomer phase and the nylon matrix is ​​improved, the interfacial bonding is stronger, and the tensile strength, flexural strength, and heat distortion temperature of the material are slightly higher than those of Example 1. This indicates that stronger interfacial bonding is beneficial to improving the load-bearing performance of the material under static load. However, stronger interfacial action will cause the elastomer phase to be more constrained, which is not conducive to the elastomer phase producing moderate deformation, interfacial stress release, and crack passivation under notched impact and low-temperature impact conditions. Therefore, the notched impact strength at 23°C and the notched impact strength at -30°C are both lower than those of Example 1.

[0048] As can be seen from the test results of Example 1 and Comparative Example 2 in Table 1, without the addition of an interface modifier, the system lacks the polyether siloxane slip interface structure formed by the reaction of monoglycidyl ether-terminated polydimethylsiloxane and diamino-terminated polyetheramine. It is difficult to form a transition layer with both limited anchoring and local slip capabilities between the elastomer phase and the nylon matrix. The interface stress release and crack passivation process under impact load are affected, so the notched impact strength at 23°C and the notched impact strength at -30°C both decrease. At the same time, insufficient interface modulation also affects the stress transfer between the elastomer phase and the nylon matrix, resulting in tensile strength, flexural strength and heat distortion temperature being lower than those of Example 1.

[0049] As can be seen from the test results of Example 1 and Comparative Example 3 in Table 1, without the addition of zinc stearate, stearic acid and deionized water, the system lacks the interfacial regulation effect jointly participated by zinc stearate, stearic acid and trace water. The stress transfer effect at the interface of maleic anhydride-grafted polyolefin elastomer is relatively weakened due to the lack of rearrangement. The local stress release ability at the interface is reduced during the impact process. Therefore, the notched impact strength at 23°C and the notched impact strength at -30°C are lower than those of Example 1. Since the interface regulator and modified nano-silica are still present, the tensile strength, flexural strength and heat distortion temperature of the material decrease relatively little, but are still lower than those of Example 1.

[0050] As can be seen from the test results of Example 1 and Comparative Example 4 in Table 1, without the addition of modified nano-silica, the elastomer phase interface lacks point support and stress dispersion adjustment structure, and the interface stress release and crack passivation effect under impact load are relatively weakened. Therefore, the notched impact strength at 23℃ and the notched impact strength at -30℃ are both lower than those of Example 1. At the same time, modified nano-silica contributes to the interface support and flexural load-bearing capacity. Without this component, the flexural strength and heat distortion temperature of the material are also reduced, and the tensile strength is also lower than that of Example 1.

[0051] As shown in Table 1, when maleic anhydride-grafted POE, interface modifier, zinc stearate, modified nano-silica, stearic acid, deionized water, and compound antioxidant are directly blended with the nylon matrix without pre-preparing toughening masterbatch, the functional components are more likely to be randomly dispersed in the nylon matrix, which is not conducive to their participation in the construction of the interface structure near the elastomer phase. This results in a weakening of the synergistic regulatory effect of the interface modifier, zinc stearate, and modified nano-silica near the elastomer phase interface. Therefore, the notched impact strength at 23°C and the notched impact strength at -30°C are both lower than those in Example 1. At the same time, due to insufficient pre-construction of the interface structure, the stress transfer and interface stability between the elastomer phase and the nylon matrix decrease, and the tensile strength, flexural strength, and heat distortion temperature are also lower than those in Example 1.

[0052] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A high-impact nylon composite material, characterized in that, The high impact-resistant nylon composite material is obtained by melt blending a nylon matrix, toughening masterbatch, and compounded antioxidant. The nylon matrix is ​​composed of pre-dried PA66 and PA6; The toughening masterbatch is obtained by reactive extrusion of raw materials including maleic anhydride grafted polyolefin elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water and compound antioxidant. The maleic anhydride grafting rate of the maleic anhydride-grafted polyolefin elastomer is 0.3-0.8 wt%. The interface modifier is obtained by reacting monoglycidyl ether-terminated polydimethylsiloxane with diamino-terminated polyetheramine. The modified nano-silica is obtained by modifying nano-silica with 3-aminopropyltriethoxysilane.

2. The high impact-resistant nylon composite material according to claim 1, characterized in that, The mass ratio of PA66 to PA6 is (70-90):(10-30); the mass ratio of the pre-dried nylon matrix, toughening masterbatch and compound antioxidant is 100:(14-20):(0.15-0.35).

3. The high impact-resistant nylon composite material according to claim 1, characterized in that, The mass ratio of the maleic anhydride-grafted polyolefin elastomer, interface modifier, zinc stearate, modified nano silica, stearic acid, deionized water, and compound antioxidant is 100:(10-14):(1.5-3):(3-6):(0.05-0.3):(0.05-0.2):(0.5-1.2).

4. The high impact-resistant nylon composite material according to claim 1, characterized in that, The maleic anhydride-grafted polyolefin elastomer is any one of maleic anhydride-grafted POE, maleic anhydride-grafted EOR, or maleic anhydride-grafted EPDM.

5. The high impact-resistant nylon composite material according to claim 1, characterized in that, The double-terminated amino polyetheramine is polyetheramine D-230 or polyetheramine D-400; the compound antioxidant is obtained by compounding antioxidant 1098 and antioxidant 168 in a mass ratio of (1-3):

1.

6. A method for preparing a high-impact nylon composite material according to any one of claims 1-5, characterized in that, Includes the following steps: S1: After drying, nano-silica is dispersed in a mixed solvent, the pH is adjusted and ultrasonically dispersed, 3-aminopropyltriethoxysilane is added to react, and after centrifugation, washing and drying, modified nano-silica is obtained. S2: A monoglycidyl ether-terminated polydimethylsiloxane and a diamino-terminated polyetheramine are reacted under nitrogen protection and then vacuum devoured to obtain an interface modifier; S3: Mix the interface modifier, zinc stearate, modified nano silica, stearic acid and deionized water to obtain a premix; dry the maleic anhydride-grafted polyolefin elastomer and knead it with the premix to obtain an elastomer premix; react and extrude the elastomer premix and compound antioxidant to obtain toughening masterbatch. S4: PA66 and PA6 are mixed and dried to obtain a pre-dried nylon matrix; the pre-dried nylon matrix, toughening masterbatch and compound antioxidant are mixed and melt-blended to obtain a high-impact nylon composite material.

7. The preparation method according to claim 6, characterized in that, In step S1, nano-silica is vacuum dried at 100-120℃ for 2-4 hours to obtain pre-dried nano-silica; the volume ratio of ethanol to water in the mixed solvent is (80-95):(5-20), and the mass-volume ratio of pre-dried nano-silica to the mixed solvent is 1g:(20-60)mL; the pH is adjusted to 4.0-5.5; ultrasonic dispersion is performed for 20-60 minutes; the mass ratio of 3-aminopropyltriethoxysilane to pre-dried nano-silica is (3-10):100; the reaction temperature is 45-70℃, and the reaction time is 3-6 hours; the drying temperature is 70-90℃, and the drying time is 6-12 hours.

8. The preparation method according to claim 6, characterized in that, In S2, the molar ratio of epoxy groups derived from monoglycidyl ether-terminated polydimethylsiloxane to the molar ratio of diamino-terminated polyetheramine molecules is 1:(1.2-2); the reaction temperature is 60-90℃, and the reaction time is 3-8h; the vacuum devolatilization temperature is 80-100℃, the vacuum degree is -0.08~-0.095MPa, and the vacuum devolatilization time is 0.5-2h.

9. The preparation method according to claim 6, characterized in that, In S3, the mixing temperature is 40-70℃, and the mixing time is 10-30 min; the drying temperature is 60-90℃, and the drying time is 2-4 h; the premix kneading temperature is 50-80℃, and the premix kneading time is 20-60 min; the parameters of the reactive extrusion are: temperature 175-210℃, screw speed 150-320 rpm, and material residence time 1-4 min. The reactive extrusion includes a melting reaction section and a vacuum exhaust section located in the middle or rear section, with a vacuum exhaust pressure of -0.06~-0.095 MPa.

10. The preparation method according to claim 6, characterized in that, In S4, PA66 and PA6 are mixed and then vacuum dried at 90-110℃ for 8-12 hours. The parameters for the melt blending are as follows: extrusion temperature is 250-285℃, wherein when the mass percentage of PA6 in the pre-dried nylon matrix is ​​greater than 20%, the extrusion temperature is 250-275℃, and when the mass percentage of PA6 in the pre-dried nylon matrix is ​​10-20%, the extrusion temperature is 260-285℃; screw speed is 180-350rpm, material residence time is 1-3min, and vacuum exhaust pressure is -0.06~-0.095MPa.

Citation Information

Patent Citations

  • Epoxy resin composition as well as preparation method and application thereof

    CN114806077A

  • Nylon-based heat-conducting composite material and preparation method thereof

    CN122234597A